TATA KERJA ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KOTA PEKANBARU TAHUN 2014-2016 - Khusnul Khotimah; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In a democratic country, the existence of the House of Representatives (DPR) and the Regional House of Representative (DPRD) or legislative body is a must, because the legislative body is the people's representative in making the Law as well as the Regional Regulation that will be applied to the people. DPRDs have legislative, budgetary, and supervisory functions. Identification of problems found are: lack of discipline in attending DPRD meetings, poor performance of DPRD members Pekanbaru, Being less polite and not maintaining order at every DPRD meeting, leaving the meeting before the meeting is finished. This study aims to describe the implementation of the working procedures of members of Parliament Pekanbaru City and know the factors inhibiting the implementation of working procedures of DPRD members Pekanbaru Year 2014-2016. This research uses a qualitative approach and descriptive research type. Based on the result of the research, it is found that the working procedure of DPRD member of Pekanbaru City has not been optimal, such as the low level of attendance of the board members, the low draft local regulations from the Pekanbaru City DPRD initiative, the low level of supervision and the lack of recess time. Inhibiting factors in the implementation of work procedures are: lack of professional members of the board, the schedule of the colliding work agenda, lack of discipline over time and lack of communication both between the members of the council itself and between DPRD fittings.Keywords: Work Procedure, Regional House of Representatives